solve the following pair of equation by the method of elimination7(y+3)-2(x+2)=14 ; 4(y-2)+3(x-3)=2
please answer....please
Answers
Answered by
1
Hi !
7(y+3) -2(x+2) = 14
7y + 21 - 2x -4 = 14
7y - 2x + 17 = 14
7y - 2x = -3 ------> [1]
==============================
4(y - 2) +3(x-3)=2
4y - 8 + 3x - 9 = 2
4y + 3x - 17 = 2
4y + 3x = 19 -----> [2]
7y - 2x = -3
4y + 3x = 19
lets make the coefficients of the variable x equal .
3(7y - 2x = -3 )
2(4y + 3x = 19 )
the equation becomes :
21y - 6x = -9 ----> [3]
8y + 6x = 38 ----> [4]
adding equations 3 and 4 ,
21y - 6x = -9
+ 8y + 6x = 38
------------------------
29 y = 29
y = 29/29 = 1
put this value in equation [2]
4y + 3x = 19
4 + 3x = 19
3x = 15
x = 15/3
x = 5
hence ,
x = 5 , y = 1
7(y+3) -2(x+2) = 14
7y + 21 - 2x -4 = 14
7y - 2x + 17 = 14
7y - 2x = -3 ------> [1]
==============================
4(y - 2) +3(x-3)=2
4y - 8 + 3x - 9 = 2
4y + 3x - 17 = 2
4y + 3x = 19 -----> [2]
7y - 2x = -3
4y + 3x = 19
lets make the coefficients of the variable x equal .
3(7y - 2x = -3 )
2(4y + 3x = 19 )
the equation becomes :
21y - 6x = -9 ----> [3]
8y + 6x = 38 ----> [4]
adding equations 3 and 4 ,
21y - 6x = -9
+ 8y + 6x = 38
------------------------
29 y = 29
y = 29/29 = 1
put this value in equation [2]
4y + 3x = 19
4 + 3x = 19
3x = 15
x = 15/3
x = 5
hence ,
x = 5 , y = 1
Similar questions